2010
DOI: 10.1016/j.jcin.2009.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Multiple and Long Sirolimus-Eluting Stent Implantation on 3-Year Clinical Outcomes in the j-Cypher Registry

Abstract: TSL per lesion and patient had significantly impacts on TLR rates. Longer TSL per patient was associated with increased incidence of stent thrombosis through 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…Surprisingly, neither group showed any association between stent length and restenosis. This is an unexpected finding since several previous studies have shown a correlation between stent length and/or placement of multiple stents with restenosis, particularly with BMS [1][2][3][4][5][6][7][8][9][10][11][12]. Many of these studies evaluated early generation BMS, comparisons were made to short, focal coronary lesions, and the definition of "long lesions" was conservative compared to our study.…”
Section: Discussionmentioning
confidence: 48%
“…Surprisingly, neither group showed any association between stent length and restenosis. This is an unexpected finding since several previous studies have shown a correlation between stent length and/or placement of multiple stents with restenosis, particularly with BMS [1][2][3][4][5][6][7][8][9][10][11][12]. Many of these studies evaluated early generation BMS, comparisons were made to short, focal coronary lesions, and the definition of "long lesions" was conservative compared to our study.…”
Section: Discussionmentioning
confidence: 48%
“…It is known that the stented length is a strong predictor of events at follow-up, such as stent thrombosis and need for repeat revascularization. 53,54 Additionally, the permanent caging of the artery inhibits the recovery of the physiological properties of the vessel. In CTO PCI, BVS could have obvious advantages compared with metallic stents by fully avoiding the problems arising from having permanent metal caging in the vessel.…”
Section: Bvs In Chronic Total Occlusionsmentioning
confidence: 99%
“…The definitions of the variables and estimated outcomes were described in the text. lesions (29), diffuse lesions were treated with long stents (mean length >33 mm) (30), and the bifurcation two-stent technique was used in approximately 7-8% of lesions (15,29). Although the mean late loss after PES placement was significantly larger than that after SES placement, the larger late loss in the PES group did not translate into significantly higher ISR and TLR ratios compared to those of SES after the baseline adjustment (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Second, because this was a lesion-based study, patient-based severe cardiac events, an important issue in estimating the safety of novel stent, were not fully investigated. There were only small percentages of lesion-based severe cardiac events during a mean follow-up period of approximately 540-550 days, but it would be acceptable to compare these results with reports from Western countries about SES and prior TAXUS Express stents (3-5) because we included various consistent predictors of severe cardiac events and restenosis as discussed above (27)(28)(29)(30). Third, the duration of dual anti-platelet therapy and the choice of thienopyridine agent (ticlopidine or clopidogrel) depended on the doctor's judgment.…”
Section: Sesmentioning
confidence: 99%